Update on Transumbilical Single-Incision Laparoscopic Assisted Appendectomy (TULAA) – Which Children Benefit and What are the Complications? - Dübbers, Martin; Nikolaou, Elena; Fuchs, Hans; Fischer, Janina; Alakus, Hakan; Leers, Jessica; Bruns, Christiane; Cernaianu, Grigore (Klinische Pädiatrie, 2018)
Background Transumbilical laparoscopic-assisted appendectomy (TULAA) is fast and cost-effective since no endoloops, staplers or wound protection devices are used. We analyzed the effects of TULAA as first approach for perforated (PA) and non-perforated (NPA) appendicitis in children.Patients We performed a retrospective analysis of 181 children for whom TULAA was the first approach for appendicitis between October 2010 and March 2016. Methods Morbidity, additional laparoscopic instrument insertion (AI), conversions to open extraumbilical appendectomy (OC), and complications were evaluated.Results TULAA was initiated in 181 (87.4%) children (113 boys: 68 girls). Median age was 10.3 years (3.3–13.9 years) and BMI 16.8 kg/m2 (12.4–30.8). Appendicitis was non-perforated in 157 (86.7%) and perforated in 24 (13.3%) patients. TULAA was finalized in 142 (78.5%) patients, AI were inserted in 20 (11%) and OC were performed in 19 (10.5%) patients. Duration of surgery did not exceed 20 min for 12.8%, and 30 min for 43.6% of patients with TULAA and NPA. The rate of wound infections did not differ between procedures (TULAA 3/142 (2.1%), AI 0 (0%), OC 1/19 (5.3%), P=1.000). Further postoperative course was uneventful in 179 (98.9%) patients.Conclusion TULAA can be used as first approach for appendicitis in all children with a low rate of complications. Extracorporeal appendix stump closure can be safely achieved in the majority of children without using laparoscopic disposable devices.
Keywords: appendicitis; children; single incision; TULAA